2018
DOI: 10.1016/j.jtho.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Training and Validating a Portable Electronic Nose for Lung Cancer Screening

Abstract: This feasibility study showed that this portable e-nose can properly differentiate between patients with lung cancer and healthy controls. This result could have important implications for future lung cancer screening. Further studies with larger cohorts, including also more participants with early-stage tumors, should be performed to increase the robustness of this noninvasive diagnostic tool and to determine its added value in the diagnostic chain for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 27 publications
(34 reference statements)
0
74
0
Order By: Relevance
“…Previous studies have shown that electronic nose technology based on pattern recognition of VOCs or identifying VOCs with gas chromatography/mass spectrometry can differentiate between subjects with and without lung cancer [13,14,17,20,[27][28][29]. Several studies using techniques for VOC identification have used logistic regression analysis to identify lung cancer-specific VOCs [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that electronic nose technology based on pattern recognition of VOCs or identifying VOCs with gas chromatography/mass spectrometry can differentiate between subjects with and without lung cancer [13,14,17,20,[27][28][29]. Several studies using techniques for VOC identification have used logistic regression analysis to identify lung cancer-specific VOCs [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…VOCs are of interest since they might be directly related to the presence of diseases, they can be tested noninvasively and pattern recognition techniques can serve as classifiers for diseases. Several studies on exhaled-breath analysis have supported the hypothesis that VOC patterns alter when lung cancer is present [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…Patient conditioning also varied between studies. In Wang's study participants did not eat or smoke for 12 hours prior to sampling, whereas Van der Goors' study had no such limitations, 126,130 . These differences make combining data to apply conclusions to a large population very difficult.…”
Section: Clinical Research To Datementioning
confidence: 99%
“…Circulating free DNA seems more suitable for determining driver gene mutations rather than for early diagnosis; likewise, circulating tumour cells are able to differentiate histology in metastatic disease [133]. "Electronic nose" techniques showed a specificity of 71%-100% and a sensitivity of 74%-86%, although mostly in advanced disease [135]. Furthermore, they still suffer from variability.…”
Section: Molecular Biomarkersmentioning
confidence: 99%